2017
DOI: 10.1111/nph.14840
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative mesophyll parameters rather than whole‐leaf traits predict response of C3 steppe plants to aridity

Abstract: We studied the impact of aridity on leaf and mesophyll traits in dominant and very abundant plant species of Eurasian steppe plant communities. We covered a 500-km latitudinal gradient across three vegetation zones in the Volga region of southern European Russia. Whole-leaf traits, volumetric fractions of leaf tissues, quantitative parameters of photosynthetic cells and chloroplasts, and chlorophyll, carbon (C) and nitrogen (N) contents were analyzed and related to plant functional type (PFT), type of mesophyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 50 publications
6
35
0
4
Order By: Relevance
“…Cell projection area and perimeter were measured separately for each type of photosynthetic tissue (palisade and spongy mesophyll for C 3 -plants, mesophyll and bundle sheath cells for C 4 -plants, simple and segmented mesophyll cells for grasses) with a light microscope (Axiostar plus, Zeiss, Germany) and the image analysis system SIAMS Mesoplant (SIAMS, Yekaterinburg, Russia). The mesophyll cell volume (V cel , 10 3 μm 3 ) and the chloroplast volume (V chl, μm 3 ) as well as their surface areas (S cel , 10 3 μm 2 , and S chl , μm 2 ) were calculated by the projection method described in detail by Ivanova and Pyankov (2002) and Ivanova et al (2018). Chloroplast number per cell (Chl per cell) was determined in 30 replicates per sample in the same cells that were measured for cell sizes.…”
Section: Leaf Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell projection area and perimeter were measured separately for each type of photosynthetic tissue (palisade and spongy mesophyll for C 3 -plants, mesophyll and bundle sheath cells for C 4 -plants, simple and segmented mesophyll cells for grasses) with a light microscope (Axiostar plus, Zeiss, Germany) and the image analysis system SIAMS Mesoplant (SIAMS, Yekaterinburg, Russia). The mesophyll cell volume (V cel , 10 3 μm 3 ) and the chloroplast volume (V chl, μm 3 ) as well as their surface areas (S cel , 10 3 μm 2 , and S chl , μm 2 ) were calculated by the projection method described in detail by Ivanova and Pyankov (2002) and Ivanova et al (2018). Chloroplast number per cell (Chl per cell) was determined in 30 replicates per sample in the same cells that were measured for cell sizes.…”
Section: Leaf Traitsmentioning
confidence: 99%
“…Instead of individual parameters of cells or chloroplasts, the most promising traits are integral parameters of photosynthetic tissues as the total chloroplast number per leaf area (N chl /A) and the total surface area of chloroplasts (A chl /A) and cells (A mes /A) per leaf area. These functional leaf traits were shown to predict the response of C 3plants to climate in different climatic zones inside Russia-European steppes (Ivanova et al, 2018). The site-mean values of N chl /A, A chl /A and A mes /A were higher in steppe than in boreal plants, and in C 3 -plants growing in the desert steppe compared with those of the forest steppe.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…This diffusion pathway is complex, as it involves air, aqueous and lipid phases; namely intercellular air spaces, cell walls, plasma membrane, cytosol, chloroplast membrane, and stroma. In a recent study, Ivanova et al (2018) quantitatively analyzed the internal structures of leaves from many C3 steppe plant species using only chemical and microscopy techniques. They concluded that larger mesophyll and chloroplast surface areas per total leaf area (S c /S) were very indicative of plant adaptation to increasing aridity, speculating on the relationship between these characters and g m , photosynthesis, etc.…”
Section: What Can Ecophysiology Do For the 'Omics' Community And Vicementioning
confidence: 99%
“…Mesophyll conductance is generally lower in leaves with thicker cell walls and greater leaf density (Adachi et al 2013, Ivanova et al 2018) that are conditions limiting the diffusion of CO 2 in the leaf liquid phase (Tomás et al 2013, Onoda et al 2017). Ozone may affect leaf morphology, which is likely to modify the CO 2 diffusion inside leaves (Heath 1994, Moura et al 2018).…”
Section: Introductionmentioning
confidence: 99%